Description of Dorylaimoides alborzicus sp. n. (Dorylaimida: Nematoda) from Iran, with updated compendium and key to the species of Dorylaimoides - Pedram, Majid; Pourjam, Ebrahim; Vinciguerra, Maria T. (Zootaxa, 2011)
Dorylaimoides alborzicus sp. n. is described. Characteristics of the new species include a lip region separated from the rest of body by a sharp constriction, 1.1–1.3 mm long body, 10–11 µm long odontostyle dorsal line and 8–10 µm long odontostyle ventral line, 15–16 µm long arcuate odontophore, anterior uterine sac 37–61 µm long (1.1–1.7 times corresponding body width), female tail straight to ventrally bent, elongate conoid with rounded terminus and 46–62 µm long and males with 31–35 µm long spicules, 5–6 ventromedian supplements and ventrally bent tail, 39–60 µm long. An updated identification key to all the valid species of Dorylaimoides, as well as a table of data for the species not included in the study by Peña Santiago and Peralta (1997b) is given.